Meningkatkan kemampuan menghafal juz amma melalui media pembelajaran audio visual - Desyanti Desyanti; Mustazihim Suhaidi; Fitra Fitra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Learning is a process of communication between learners, instructors and teaching materials. SDIT ATH-THAARIQ 2 Dumai is one of the integrated Islamic elementary schools in the city of Dumai, has a vision of realizing the Qur'anic generation, Islamic civilization, intelligent, high achievers, towards global-minded human beings. SDIT ATH-THAARIQ 2 Dumai familiarizes students with praying in congregation and dhuha prayers every day, practicing Islamic customs such as eating and drinking, going to the toilet, adab to old people, procedures for taking the right and memorizing methods juz amma. Teaching and learning activities currently still use book and blackboard media. This makes students less interested and bored during the learning process, thus giving the effect of lazy learning which results in a decrease in students' ability to absorb lessons. Learning media are designed according to the needs and attractive appearance, in the application are designed lightweight games to eliminate boredom in students and facilitate students in memorizing. The application design is made using Adobe Photoshop CS6 software, and Adobe Flash Professional CS6. This application can improve students 'ability in memorizing juz amma and understand how to take whudu correctly so that it makes it easier for teachers in the learning process. Students' abilities increase by 50% and boredom during learning can be overcome by the existence of such learning media, because the display in the application is easily understood by students.